ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS III SD NEGERI 01 KARANG MELATI - Klara Novena Murwani; Neta Dian Lestari; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
His study aims to describe and determine the level of mathematical concept understanding ability of data presentation material in tables of grade III students of SD Negeri 01 Karang Melati. The subjects of this study were grade III students of SD Negeri 01 Karang Melati involving 12 students who were taken based on the criteria of very good, good, sufficient and less. The research method used in this study is a qualitative method. In analyzing the data, this study used a qualitative descriptive approach. Data collection techniques used were interviews and documentation of students' daily test results. From the results of the study and analysis, it can be seen that the mathematical concept understanding ability of grade III students of SD Negeri 01 Karang Melati on data presentation material in tables is divided into 4 categories, namely the indicator restating the concept that has been learned is included in the very good category, the indicator classifying objects based on whether or not the requirements that form the concept are met is included in the good category, the indicator applying concepts logically is included in the sufficient category and the indicator presenting concepts in various forms of mathematical representation (tables, graphs, diagrams, pictures, sketches, mathematical models or other methods) is included in the less category. At the end of the study, the results showed that students' mathematical concept understanding ability on data presentation material in tables was included in the fairly good category.